Impacts of local adaptation of forest trees on associations with herbivorous insects: implications for adaptive forest management - Sinclair, Frazer H; Stone, Graham N; Nicholls, James A; Cavers, Stephen; Gibbs, Melanie; Butterill, Philip; Wagner, Stefanie; Ducousso, Alexis; Gerber, Sophie; Petit, Rémy J; Kremer, Antoine; Schönrogge, Karsten (Evolutionary applications, 2015)
Disruption of species interactions is a key issue in climate change biology. Interactions involving forest trees may be particularly vulnerable due to evolutionary rate limitations imposed by long generation times. One mitigation strategy for such impacts is Climate matching - the augmentation of local native tree populations by input from nonlocal populations currently experiencing predicted future climates. This strategy is controversial because of potential cascading impacts on locally adapted animal communities. We explored these impacts using abundance data for local native gallwasp herbivores sampled from 20 provenances of sessile oak (Quercus petraea) planted in a common garden trial. We hypothesized that non-native provenances would show (i) declining growth performance with increasing distance between provenance origin and trial site, and (ii) phenological differences to local oaks that increased with latitudinal differences between origin and trial site. Under a local adaptation hypothesis, we predicted declining gallwasp abundance with increasing phenological mismatch between native and climate-matched trees. Both hypotheses for oaks were supported. Provenance explained significant variation in gallwasp abundance, but no gall type showed the relationship between abundance and phenological mismatch predicted by a local adaptation hypothesis. Our results show that climate matching would have complex and variable impacts on oak gall communities.
Keywords: gallwasp; provenance trials; adaptive forest management; population nonindependence; Quercus petraea; climate matching; plant–insect interactions; local adaptation